Analysis of Needs For Self-Assessment and Diagnostic Assessment of Differentiation Learning In Primary School - Sukamto, Sukamto; Waluya, ST. Budi; Rusilowati, Ani; Masrukan, Masrukan (Proceedings of International Conference on Science, Education, and Technology, 2024)
This research is motivated by learning in schools which is still teacher-centered, so that learning does not match students' interests and learning needs. The research aims to analyze teachers' needs in designing differentiated learning that accommodates all elementary school students' learning needs. The research method used in this research is descriptive qualitative. Researchers developed a questionnaire instrument that was given and filled out by prospective elementary school teacher students who were studying professional teacher education at universities in Semarang City. The results of the analysis of the questionnaire that had been filled out by respondents showed that prospective elementary school teachers still needed self-assessment and diagnostic assessment models for differentiated learning that could accommodate the learning needs of elementary school students. To be able to carry out differentiated learning, teachers need more detailed information about student profiles through student self-assessments and diagnostic assessments carried out by teachers so that learning will run effectively according to students' abilities, interests and learning abilities.